Description of a new species of Heydenia Förster, 1856 (Hymenoptera: Heydeniidae) from Southern India with two new distributional records - M., Hemanth Kumar H.; Gupta, Ankita; Sharma, Adarsh (Zootaxa, 2025)
In the present study, one new species, Heydenia longipetiolata Hemanth & Gupta sp. nov. (Hymenoptera: Chalcidoidea: Heydeniidae), is described and illustrated from Karnataka, India, as a solitary larval parasitoid of Agrilus spp. (Coleoptera: Buprestidae) infesting branches of Villebrunea integrifolia Gaud. (Urticaceae) and Albizia amara (Roxb.) Boivin. (Fabaceae), respectively. Two species, H. gibsoni Sureshan, 2009, previously known from Sri Lanka, and H. testacea Yang, 1996, previously known from China, are recorded from India for the first time. Additionally, H. kashmirensis Sureshan & Khanday, 2021, previously known from Jammu and Kashmir (Northern India), is recorded from Karnataka (Southern India). An undetermined species of Heydenia resembling Heydenia angularicoxa Yang, 1996 is also included in the present paper and an illustrated diagnosis is provided for all the species. An identification key to all the known Indian species of Heydenia Förster, 1856 is also provided.